A tetravalent nanoparticle vaccine elicits a balanced and potent immune response against dengue viruses without inducing antibody-dependent enhancement - Chen, Qier; Li, Rong; Wu, Bolin; Zhang, Xu; Zhang, Hui; Chen, Ran (Frontiers in Immunology, 2023)
Dengue fever is a global health threat caused by the dengue virus (DENV), a vector-borne and single-stranded RNA virus. Development of a safe and efficacious vaccine against DENV is a demanding challenge. The greatest pitfall in the development of vaccines is antibody-dependent enhancement (ADE), which is closely associated with disease exacerbation. We displayed the modified envelope proteins from the four serotypes of the DENV on a 24-mer ferritin nanoparticle, respectively. This tetravalent nanoparticle vaccine induced potent humoral and cellular immunity in mice without ADE, and conferred efficient protection against the lethal challenge of DENV-2 and DENV-3 in AG6 mice. Further exploration of immunization strategies showed that even single-dose vaccination could reduce pathologic damage in BALB/c mice infected with high doses of DENV-2. Treatment with cyclic-di-guanosine monophosphate facilitated a higher titer of neutralizing antibodies and a stronger type-1 T-helper cell-biased immune response, thereby revealing it to be an effective adjuvant for dengue nanoparticle vaccines. These data suggest that a promising tetravalent nanoparticle vaccine could be produced to prevent DENV infection.